THE THERMOELECTRIC SYSTEM MODEL FOR THERMAL COSMETIC PROCEDURES - U. I. Abdulhakimov; O. V. Evdulov (Вестник Дагестанского государственного технического университета: Технические науки)
The model of thermoelectric systems for thermal cosmetic procedures that are based on solving two-dimensional unsteady heat conduction problem for a system of complex configuration. The dependences of temperature change at different points of the object of influence – the area of the skin exposed to the heat of cosmetic procedures, depending on the cooling and heating capacity of thermoelectric modules, external conditions.